Efficacy for writing self-regulation, attitude toward writing, and quality of second grade students’ writing - Skar, Gustaf B.; Graham, Steve; Huebner, Alan R. (Frontiers in Psychology, 2023)
Motivational beliefs, such as writing self-efficacy and attitude towards writing, are believed to foster or hinder writing by influencing if one chooses to write, how much effort is committed to writing, and what cognitive resources writers apply. In the current study, we examined self-efficacy for writing self-regulation and attitude towards writing of 2,124 Grade 2 Norwegian students (1,069 girls; 1,055 boys). We investigated if there were differences in each of these beliefs between girls and boys and students who differed in their language status (Norwegian first language, Norwegian and another language both first language, or language other than Norwegian first language). We further tested if each of these writing motivational beliefs made statistically unique contributions to predicting the quality of students' writing. In each of these analyses, we controlled for variance related to individual-and school factors.Girls were more positive about writing than boys, and they were confident about their abilities to self-regulate writing. Students with Norwegian and another language both as first language ("bilingual" students) had a more positive attitude towards writing than the other two language groups. Efficacy for writing self-regulation and attitude towards writing both made statistically significant unique contributions to predicting the quality of students writing, although these two writing beliefs collectively accounted for just 2% of the variance in writing quality scores once individual-and school-factors were controlled. Recommendations for future research and implications of the finding are discussed.